Discrete Takagi-Sugeno Fuzzy Models Applied to Control the Knee Joint Movement of Paraplegic Patients - Gaino, Ruberlei; Covacic, Marcio R.; Cardim, Rodrigo [UNESP]; Sanches, Marcelo A. A. [UNESP]; De Carvalho, Aparecido A. [UNESP]; Biazeto, Anderson Ross; Teixeira, Marcelo C. M. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
In this manuscript, a method for designing Takagi-Sugeno (T-S) fuzzy discrete-time regulators based on linear matrix inequalities (LMIs) is proposed to control the variation of the knee joint angle movement of paraplegic patients through electrical stimulation. A simple method for discretizing nonlinear systems described by T-S fuzzy models is used. The control strategy is applied for a paraplegic volunteer and a healthy one. The results and analysis show that the controlled system attended the design specifications for small values of the sample time considered for the discretization.
Keywords: Takagi-Sugeno; regulators; rehabilitation engineering; discretization; LMI; paraplegic